Synthesis and Biological Activity of Succinimidobenzenesulfonyl Oxopyrrolidine Analogs as Possible Antineoplastic Agents - Ray, Supratim; Uday De, Arun (Asian Journal of Chemistry, 2010)
Some new succinimidobenzenesulfonyl oxopyrrolidine analogs were synthesized and screened for antitumor activity against Ehrlich ascites Carcinoma in female Swiss albino mice using percentage inhibition of tumor cell count and tumor weight as activity parameters. Few synthesized compounds show encouraging activity.